Factors Affecting The Behavioral Intention to Use Central Bank Digital Currency: Experimental Research in Vietnam - Nguyen Hong, Minh; Pham Nguyen Thien, Trang; Do Huong, Mai; Le Ngoc, Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the factors influencing the intention to use Central Bank Digital Currency (CBDC) in Vietnam. Through analysis of 404 survey responses from Vietnamese citizens using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results demonstrate that perceived usefulness, perceived ease of use, perceived innovativeness, and subjective norms all positively influence the intention to use CBDC. However, contrary to expectations, perceived security does not have a significant impact. Additionally, perceived usefulness plays a mediating role in the relationship between perceived ease of use, subjective norms, and usage intention. Based on these findings, the authors propose recommendations for government regulatory agencies regarding CBDC implementation to promote broader public acceptance when CBDC is officially launched in Vietnam.
Keywords: CBDC; Intention to use; Perceived innovativeness; Perceived security; Perceived usefulness